Industrial Wastewater Management in River Basins Nhue-Day and Dongnai Project : Final Report - World Bank (World Bank, 2012)
This report provides a complete and comprehensive analysis of industrial wastewater management in industrial estates and craft villages in Vietnam. The analysis was conducted in three separate stages: 1) a detailed inventory of industries and industrial activities responsible for the pollution of the Nhue-Day river basin, including industrial zones, industrial clusters, industrial points, craft villages and large-scale stand alone industries. In the Dong Nai river basin, an inventory of the industrial parks is all that exists for now; 2) an institutional and regulatory analysis in the Nhue-Day and Dong Nai river basin provinces; and 3) identification and determination of appropriate interventions for industrial estates and craft villages.